2016
DOI: 10.1038/srep28348
|View full text |Cite
|
Sign up to set email alerts
|

Selection of reliable reference genes for RT-qPCR analysis during developmental stages and abiotic stress in Setaria viridis

Abstract: Real-time PCR (RT-qPCR) expression analysis is a powerful analytical technique, but reliable results depend on the use of stable reference genes for proper normalization. This study proposed to test the expression stability of 13 candidate reference genes in Setaria viridis, a monocot species recently proposed as a new C4 model plant. Gene expression stability of these genes was assayed across different tissues and developmental stages of Setaria and under drought or aluminum stress. In general, our results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
64
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 58 publications
(91 reference statements)
5
64
1
1
Order By: Relevance
“…Additional studies revealed that the stability of these two genes was lower than that of other genes (Gu et al, 2011; Martins et al, 2016). However, compared to our data on gene expression and results of SHSP expression normalization, we do not recommend using them as reference genes under the conditions we tested.…”
Section: Discussionmentioning
confidence: 95%
“…Additional studies revealed that the stability of these two genes was lower than that of other genes (Gu et al, 2011; Martins et al, 2016). However, compared to our data on gene expression and results of SHSP expression normalization, we do not recommend using them as reference genes under the conditions we tested.…”
Section: Discussionmentioning
confidence: 95%
“…Procedures based on published methods for determination of gene expression (Martins et al ., ), cell‐wall monosaccharides (Sluiter et al ., ), lignin (Moreira‐Vilar et al ., ), growth conditions, biomass and stem microscopy are described in detail in Methods S1.…”
Section: Methodsmentioning
confidence: 98%
“…The expression level was calculated using endogenous genes SiUBC e SiSDH2 as reference (Martins et al, 2016). …”
Section: Methodsmentioning
confidence: 99%